Faktor-faktor yang berhubungan dengan pemberian susu formula pada bayi usia 0-6 bulan di wilayah kerja puskesmas Molompar Tombatu Timur Minahasa Tenggara - Rombot, Gabriella; Kandou, Grace D.; Ratag, Gustaaf A. E. (UNIVERSITAS SAM RATULANGI, 2013)
Breast milk is the best food in feeding babies at early aged. This is not because Breast Milk contains lots of nutrients butalso breast milk contains immunologic substances that protect the babies from infections. Breast feeding is the idealsource of nutrients for babies because it has a perfect and balanced composition for babies to grow. Breast feeding in developcountries has managed to save over 1,5 millions of babies each year. Based on that number WHO recommendingonly to give breast feeding to infants in the age of 4-6 months. UNICED declare that 30 thousands infants death in Indonesiaand 10 millions death babies world wide each year can be prevented through breast feeding program for around 6months. The purpose of these studies is to know the level of knowledge and jobs and also the support of husbands in givingformula to their infants around the age of 0-6 months in the region of health center in molompar east tombatu. Thisresearch was used Cross-Sectional methods. Samples are taken in Health Center in molompar east tombatu. The result ofthis studies shows that the respondent have a good knowledge on formula feeding and some of the respondent gives apositive feed back about the importance of breast feeding during 6 months. Some respondent with positive feed back innot to give formula to infant are unemployed. Advice that can be given is to give public counseling to society particularlymothers who are pregnant about the importance of breast feeding in infatnts and also to their husbands as well.Keywords: Factors that are associated with formula, feeding in infants aged 0-6 months